Randupitu Village Government Strategy in Pasuruan Regency in Waste Management - Aliefia, Vony; Wibawani, Sri (Faculty of Social Science, Universitas Negeri Padang, 2025)
Strategy serves as a system that can regulate the existing power and resources through public organizations (government) aimed at the public interest .The purpose of this study was to describe the strategy of the Randupitu village government of Pasuruan Regency in waste management at TPS 3R Pempes. This type of research uses a qualitative descriptive approach with data collection techniques by observation, in depth interview, and documentation. The focus of this research is based on Geoff Mulgan's (2009) government strategy theory: purposes, environment, direction, action, and learning. The results showed (1) The establishment of TPS 3R Pempes was in accordance with the needs of the community, (2 From the internal and external environmental factors, all parties have been optimally involved and play an important role in implementing the 3R principles, but there are still obstacles, (3) the direction carried out was clear and in line with the objectives, (4) waste management was optimal by producing the main product, namely Rdf. However, the application of the 3R principle in the community is still low, and (5) regular evaluations are carried out between stakeholders. Overall, this strategy shows the synergy between planning, action, evaluation, and participation that forms sustainable village environmental governance.